2016
DOI: 10.1007/s10661-016-5372-6
|View full text |Cite
|
Sign up to set email alerts
|

Desorption and mobilization of three strobilurin fungicides in three types of soil

Abstract: Phenamacril (JS399-19 with independent intellectual property developed by China), azoxystrobin, and kresoxim-methyl are strobilurin fungicide. Due to their broad spectrum and good control of most of known fungi, strobilurin fungicide has been widely used in agriculture management. Thus, it is important to evaluate their environmental behaviors particularly in soils and underground water. In this study, the sorption/desorption and mobility of strobilurin fungicides in three Chinese soils (Jiangxi red soil, Taih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Current results have given negative values for ΔG for MBC adsorption into the soils, consistent with other fungicides, e.g. 14Cpyraoxystrobin (Liu et al 2018) and strobilurin fungicides (Wu et al 2016). A negative value of ΔG for MBC adsorption shows that MBC molecules were not tightly bound to the interlayer of soils selected for adsorption, and that they were held together by temporary weaker bonds, e.g.…”
Section: Mbc Physiosorptionsupporting
confidence: 79%
See 1 more Smart Citation
“…Current results have given negative values for ΔG for MBC adsorption into the soils, consistent with other fungicides, e.g. 14Cpyraoxystrobin (Liu et al 2018) and strobilurin fungicides (Wu et al 2016). A negative value of ΔG for MBC adsorption shows that MBC molecules were not tightly bound to the interlayer of soils selected for adsorption, and that they were held together by temporary weaker bonds, e.g.…”
Section: Mbc Physiosorptionsupporting
confidence: 79%
“…Other investigations on hydrophobic fungicides are indicative of lower mobility patterns as in the case of pyraoxystrobin (Liu et al 2018). In this regard, various researchers have also employed ground ubiquity score (GUS) and suggested that GUS < 1.8 ensures minimum leaching (Wu et al 2016). The current investigation of MBC adsorption in selected soils provides important information about its behavior in soils.…”
Section: Reliance Of Mbc Adsorption On Soils' Physical and Chemical F...mentioning
confidence: 97%
“…Some soil factors, including pH, organic matter [42,53,57,58], and soil amendment [59], impact the adsorption of pesticides. Moreover, soils rich in organic matter or clay are much more adsorptive to pesticides than coarse, sandy soils, because clay or organic soils either have a greater particle surface area, or more sites onto which insecticides can be bound [45,55,60,61] For example, the adsorption and desorption abilities of endosulfan may be related to the contents of clay and organic matter in the soil [46,62]. The study shows the sorption/desorption and mobility of strobilurin fungicides in three Chinese soils in the order of Jiangxi red soil > Taihu paddy soil > Northeast China black soil.…”
Section: Pesticide Migration 621 Sorptionmentioning
confidence: 99%
“…To explain the difference in behaviour evaluated through environmental availability (DMX less available than EPX) and adsorption studies (DMX more available than EPX), two reasons can be hypothesized. First, a hysteresis phenomenon could occur, decreasing DMX desorption as previously observed for some other strobilurin fungicides (Reddy et al 2013, Wu et al 2016Liu et al 2018). The second hypothesis is based on potential interactions driving pesticides remobilisation from soil, independantly of their solubilisation.…”
Section: Evaluation Of Environmental Availabilitymentioning
confidence: 82%